“To be honest, I’m pretty fat. Actually, I’m very fat”. Adjective fat as a Representation of the Concept of Obesity (Based on Corpus Data) – Preliminary Remarks - Pazio-Wlazłowska, Dorota (Vilnius University Open Series, 2021)
The article attempts to reconstruct the concept of obesity on the example of the adjective fat as one of its lexical representation. As a material for analysis, the texts of contemporary fiction (1990s–XXI century) obtained from the National Corpus of the Polish Language are used. An overweight people are characterized in the extracted material in physical, mental, aesthetic and social aspects. In the physical aspect, the face, teeth, hairstyle, hair color and appearance, height and size, as well as the physical activity are examined. Symptomatic for the physical aspect is the use of intensifiers: very obese, unbelievably obese, indecently obese. Within the mental aspect, character traits, intellectual potential, self-esteem and drug addiction are analysed. In the social aspect, attention is paid to the reluctant attitude of the environment towards obese people, the relationship of obese people with the opposite sex, as well as the main fields of activity, mainly excessive eating. As part of the aesthetic aspect, auditory, visual and olfactory impressions are analyzed. In the course of analysis lexical units used to characterize obese people are identified. The analysis shows that obese people are repulsive, unaesthetic, they smell badly and look unattractive, they eat all the time and move with difficulty. They are usually friendly and kind, but they have complexes about their looks.
Keywords: concept; obesity; fat; evaluation; Polish Language; corpus; fiction